Evaluation of new bone formation in rabbit calvarial defects induced by silk fibroin scaffolds coated with fibronectin and decellularized dental pulp - Thanh Huy Thai (Prince of Songkla University, 2018)
Thesis (M.Sc., (Oral and Maxilofacial Surgery)) Prince of Songkla University, 2016